An investigation of the relationship between drug consumption and crime in South Africa : implications for social work - Da Rocha Silva, Lee (University of Limpopo, 2004)
Refer to the document
Thesis (PhD. (Social Work)) --University of the North, 2004.
Keywords: Drug consumption; Crime; Social Work; Drug utilization; Social work with drug addicts; Crime -- South Africa; Drug abuse and crime -- South Africa